Analysis of Human Resources Management in the Montenegrin Judiciary - World Bank Group (World Bank, Washington, DC, 2016)
The Montenegrin judiciary’s strategic goals can only be accomplished through better human resource management. The sector needs a strategic approach to human resources management that links it to the judicial branch’s organizational strategy, focuses it on providing services to court users in an efficient manner, and recognizes that employees are a key asset of the courts. Overall, approximately seventy eight percent of the justice sector’s budget is devoted to personnel; only six European Union (EU) countries allocate a higher proportion of their justice sector budget to people. Nonetheless, some budget users and the justice sector in total spend more than their annual appropriation for human resources. Montenegro has the highest ratio of judges-to-population and an above average ratio of staff-to-judges compared with the twenty six EU Countries for which Commission for the Efﬁciency of Justice (CEPEJ) reported data. Setting the appropriate number and properly allocating judges, prosecutors, and staff between courts and PPOs in line with caseload will improve the efficiency of the judiciary and provide more equitable public access. The system should invest in and foster specialized and analytic roles, such as judicial and prosecutorial assistants, court managers, Information and Communication Technologies (ICT) administrators, budget analysts, and statisticians – the so called missing middle. In particular, judicial and prosecutorial assistants make an important contribution to sector performance, and they deserve special attention in HR reforms. Systems for the evaluation and discipline of judges and prosecutors have been developed; that for judges is being piloted. There is an acute need for training and capacity building across the judiciary. Overall, the judiciary needs clearer assignment of responsibility for human resources policy making, more sophisticated management, and better-defined systems for human resources than are currently in place.